The travel consumer - Mimoso, Maria João (2018)
Given the increase in intra-Community travel, in particular ‘package travel’, the European Union legislature felt it necessary to define a set of rules common to all States Members. In the attempt to combat the inequalities between those who hire this type of services and the companies that organise the trips. We propose to critically analyse this new legal instrument and discuss its scope of consumer protection. The European legislature intends by Directive 2015/2302 harmonise the rights and obligations arising from contracts for package travel and related travel services. It aims to create a true internal market for consumers, establishing a good balance between a high level of consumer protection and the competitiveness of enterprises. The rights of travellers will be better protected, in matters such as compensation, cancellation, assistance, among others. On the other hand, we see the standardisation of the concept of organised trips ending differences in doctrine and jurisprudence.